From female to female: Communication via chemosignals - Susanne Nehls; Elena Losse; Issa Salloum Sleibi; Maya Armin; Ute Habel; Natalia Chechko (Proceedings of the National Academy of Sciences, 2026)
In many species, chemosensory cues convey important information about reproductive status, but their role in shaping social interactions among women is less understood. Here, we combined functional neuroimaging with behavioral measures to test how chemosignals from women at different reproductive stages [menstruation, ovulation (OV), and early pregnancy (PRG)] affect social perception in female recipients across their own menstrual cycle. Chemosignal donors were screened and tracked for cycle phase (n = 59) and pregnancy status (n = 36). Female functional MRI participants (n = 33) completed a single-blind within-subject crossover design with two sessions, one during menstruation and one during ovulation. The participants rated attractiveness, desired proximity, and pregnancy status of standardized female faces while being unknowingly exposed to the axillary chemosignals. Neuroimaging analyses showed OV chemosignals to elicit greater activation across frontal, parietal, temporal, and subcortical regions, including the temporoparietal junction, insula, hippocampus, hypothalamus, and basal ganglia. PRG chemosignals were associated with more circumscribed responses, particularly in the prefrontal and cingulate areas. These effects were modulated by the recipient’s own cycle phase, with broader networks being engaged during ovulation than menstruation. Behaviorally, the participants maintained a greater distance from faces paired with PRG but approached them more closely during their own ovulation. Attractiveness ratings and pregnancy categorizations were unaffected by chemosensory condition or cycle phase. Together, these findings demonstrate that subtle chemosensory signals shape female social cognition in a cycle-dependent manner, highlighting an adaptive mechanism by which chemosensory cues guide competition, vigilance, and affiliation without necessarily altering explicit judgments.